The Amish bachelor's baby - Brown, Jo Ann (Brown, Jo Ann. Amish spinster club., 2019)
Working in Caleb Hartz<U+2019>s shop fits perfectly with Annie Wagler<U+2019>s plan to match him with her twin sister<U+2014>until Annie is drawn to him herself. But with his business, his farm and now his teenage runaway cousin and her baby, Caleb has no time for romance. Can they work together to care for mother and child<U+2014>without losing their hearts?